Uma introdução ao estudo das Funções Trigonométricas com recursos artísticos e seminários sobre a História da Matemática no 2º ano do Ensino Médio - Neves, Ranúzy Borges (2019)
The main objective of this study is to investigate whether the use of artistic methodologies effectively contributes to motivate second grade students of High School Integrated with Technical Education in Industrial Automation and Computing, at the Federal Institute of Santa Catarina, São Bento do Sul, to learn the concepts related to Mathematics, especially the content of Trigonometric Functions. In order to obtain a response to this research problem, the theoretical basis was given by several authors who discussed such topics in creativity in Mathematics classes , Art as a didactic tool, History of Mathematics and Seminars, the teacher / author of this work used parodies , played her guitar while teaching topics such as trigonometric reasons and notable angles. Then she also proposed to seminar on the History of Trigonometry, whose evaluation criteria were mastery of content and creativity. This last skill was required in order to be a distinction in any professional career nowadays, although not much explored in mathematics classes. Resources such as whiteboard, textbook, slides, videos and exercise lists were also used during the two-month teaching-learning session, ending with a Geogebra software summary by the cell phone or computer access. In the seminar presentations, several teams recounted facts of the biography and the main contributions to Trigonometry and Sciences in general of the mathematicians Hipparchus of Niceia, Claudius Ptolemy, François Viète, John Napier, Isaac Newton, Leonhard Euler and Bhaskara Akaria through artistic expressions such the music (parodies), theater, video, poem, poetry, chronic, etc. After the conclusion of the subject and in order for the students to evaluate the didactic proposal, a voluntary and anonymous questionnaire was applied. The analysis of the answers indicated that most of the students approved the methodology used, requesting it’s maintenance and extension. Through their greater participation and interaction in the classes as well as in the study in overtime, together with the quality of the presented works, it was verified that the return to the questioning initially proposed in this research was positive. This way, it was verified that the use of Art as a didactic tool in Mathematics can be a good way to increase students’ motivation in the subject.